PENGARUH KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DAN KINERJA GURU TERHADAP MUTU SEKOLAH DASAR DI KECAMATAN PORONG - Dewi Mindar Setianingsih; Erny Roesminingsih; Syunu Trihantoyo (STKIP Pesisir Selatan, 2026)
This study aims to analyze the influence of principals' managerial skills on school quality, examine the influence of teacher performance on school quality, and evaluate the combined influence of these two variables on the quality of public elementary schools in Porong District. The population in this study were all teachers and education personnel in Porong District, totaling 322 people. The sample used in this study was 178 respondents. The sampling technique used was random sampling. This study uses a quantitative approach with an ex-post facto research type. The analysis results show that the principal's managerial skills have 27.2% impact on school quality, while teacher performance has 39% impact on school quality. Simultaneously, both variables explain that the principal's managerial skills and teacher performance together have 46.6% impact on school quality. This indicates that the principal's managerial skills and teacher performance influence school quality improvement. Principal managerial skills and teacher performance significantly influence elementary school quality.